2013
DOI: 10.5897/jcreo2013.0102
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase total synthesis of cyclic pentapeptide Longicalycinin A, by using 2-chlorotrityl chloride resin

Abstract: Naturally isolated cyclic pentapeptide Longicalycinin A, which showed cytotoxicity to Hep G2 cancer cell line with an IC 50 value 13.52 μg/mL, has been successfully synthesized by solid-phase methodology with Fmoc/t-Bu protecting schemes via solution-phase macrocyclization. 2-chlorotrityl chloride resin was used as solid support. Solution phase macrocyclization of linear pentapeptide precursor was carried out by two different routes with mild and severe acidic conditions correspondingly and found that percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is a potentially useful synergistic effect in cancer treatment, and thus is a sign of a promising prospect for this molecule to be used in combination with other chemotherapeutic drugs against cancer cells [41]. Another study reported that the cyclic peptide compound C25 (Figure 6 nine amino acid residues in the sequence Cys-Val-Pro-Met-Thr-Tyr-Arg-Al totoxicity against colon cancer cells (CT26), as shown through an in vivo stu Longicalcynin A (Figure 6b) is a cyclopeptide originally isolated from Dianthus superbus [52]; the peptide with its analogues were subsequently synthesized, as reported by Ahmad Waqar et al ( 2013) [42]. The cytotoxicity of the synthesized compounds was evaluated to obtain information on the structure-activity relationship of the cyclopeptides, which could lead to the discovery of new, safer anticancer agents.…”
Section: Cyclic Peptide For Colon Cancermentioning
confidence: 84%
See 1 more Smart Citation
“…This is a potentially useful synergistic effect in cancer treatment, and thus is a sign of a promising prospect for this molecule to be used in combination with other chemotherapeutic drugs against cancer cells [41]. Another study reported that the cyclic peptide compound C25 (Figure 6 nine amino acid residues in the sequence Cys-Val-Pro-Met-Thr-Tyr-Arg-Al totoxicity against colon cancer cells (CT26), as shown through an in vivo stu Longicalcynin A (Figure 6b) is a cyclopeptide originally isolated from Dianthus superbus [52]; the peptide with its analogues were subsequently synthesized, as reported by Ahmad Waqar et al ( 2013) [42]. The cytotoxicity of the synthesized compounds was evaluated to obtain information on the structure-activity relationship of the cyclopeptides, which could lead to the discovery of new, safer anticancer agents.…”
Section: Cyclic Peptide For Colon Cancermentioning
confidence: 84%
“…Longicalcynin A ( Figure 6 b) is a cyclopeptide originally isolated from Dianthus superbus [ 52 ]; the peptide with its analogues were subsequently synthesized, as reported by Ahmad Waqar et al (2013) [ 42 ]. The cytotoxicity of the synthesized compounds was evaluated to obtain information on the structure–activity relationship of the cyclopeptides, which could lead to the discovery of new, safer anticancer agents.…”
Section: Cyclic Peptides For Cancermentioning
confidence: 99%
“…We designed different amino acids for each position of diversities R1, R2, R3, R4 and R5 for the synthesis of eighteen Longicalycinin A analogues, based on conserving lipophilic characteristic of peptides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Thus, we chose Ala, Val and Gly for position R1, Phe and Ala for position R2, Pro for position R3, Tyr (t-Bu), Ser(t-Bu) and Thr(t-Bu) for position R4 and Gly, Leu and Phe for position R5 in the first category.…”
Section: Designing Linear Peptides Of Longicalycinin a Analoguesmentioning
confidence: 99%
“…The trityl linker allows the protected compounds to be subjected to various chemical manipulations and consequently to afford pure compounds without employing numerous purification steps. [13][14][15][16][17] Oshima et al isolated a cyclic pentapeptide Longicalycinin A [cyclo-(Gly-Phe-Pro-Tyr-Phe)] from the plant Dianthus superbus var. Longicalycinus which has been used for treating carcinoma, diuretic and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This compound had been successfully synthesized by the solid-phase methodology. When acting against in vitro Dalton’s lymphoma ascites (DLA) and Enrlich’s ascites carcinoma (EAC) cells, CTC 50 values were determined to be 2.62 and 6.17 µM, respectively [ 132 ]. In the study of Tehrani et al, they demonstrated that the synthesized linear and cyclic disulfide heptapeptides of longicalycinin A showed similar inhibitory effect against HepG2 (IC 50 = 16.97 and 16.91 µM, respectively) and HT29 (IC 50 = 20.38 and 27.68 µM, respectively) cells.…”
Section: Terrestrial Plant-derived Anticancer Cyclopeptidesmentioning
confidence: 99%